Mengungkap Tingginya Turn Over Intention Pt.X Farmasi Industri - Ni Nengah Rupadi kertiriasih; Ni Luh Putu Sariani; Ida Ayu Putu Megawati; I Putu Dony Indrayana (CV. ITTC INDONESIA, 2025)
Human resources are the main subject that has a role in a company to achieve its success, so human resource management must be carried out well. Human Resources Management includes several important elements, including workforce planning, recruitment and selection, training and development, performance management, and employee compensation and welfare. Compensation includes salaries, wages and incentives related to performance and the organization. Compensation is one of the important elements in human resource management. An effective compensation system can not only motivate employees but also attract and retain the best talent in the job market. At PT. X March 2025 there will be changes in compensation, namely incentives that have decreased from previous years, incentives have decreased by almost half from previous incentives, namely following the pyramid of position hierarchy, where previously incentives were the same size and equal. This research is exploratory in nature, namely the research was carried out to explore and discover new things or knowledge in depth about how to control the level of employee turnover intention. The factors that influence turnover consist of internal and external factors. Compensation is an important component in motivating employee performance as a result of the job satisfaction they obtain. Basically, the compensation received at PT. This also results in employee dissatisfaction and decreased motivation.